2017
DOI: 10.3138/ptc.2015-45e
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Consensus on Measuring Professional Behaviour in Physical Therapy Objective Structured Clinical Examinations

Abstract: Purpose: We determined which professional behaviours (PBs) are important and feasible to measure in an objective structured clinical examination (OSCE) intended to assess the hands-on skills and knowledge of students in a Canadian physical therapy (PT) program. Methods: We used a modified Delphi technique to identify the criteria required to assess PBs in PT students during an OSCE. We conducted a focus group to better understand the results of the modified Delphi process. Results: Experienced local OSCE exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The majority of literature reviewed on the use of rating scales concentrates mainly on communication skills, professional behaviours and consultation skills . This would explain why the scores that our examiners gave for the practical station (rubber dam) were so dissimilar.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of literature reviewed on the use of rating scales concentrates mainly on communication skills, professional behaviours and consultation skills . This would explain why the scores that our examiners gave for the practical station (rubber dam) were so dissimilar.…”
Section: Discussionmentioning
confidence: 97%
“…A fast increase in the number of newly graduate physiotherapists has also been observed, who are usually inserted in the labor market with very little experience in clinical environments [43]. In a complementary way, Davies et al [44] pointed out that students in the rehabilitation area reported that many times they are not really sure of what is expected from them concerning their clinical skills and competences. Regulating agencies such as the Physiotherapy and Occupational Therapy Federal and Regional Councils, in their Ethics and Deontology Codes, provide basic norms, regulations and conducts linked to the fundamental beliefs or values of the profession, which are undertaken through the professional socialization that one student experiences when taking part in an environment of practice [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In a complementary way, Davies et al [44] pointed out that students in the rehabilitation area reported that many times they are not really sure of what is expected from them concerning their clinical skills and competences. Regulating agencies such as the Physiotherapy and Occupational Therapy Federal and Regional Councils, in their Ethics and Deontology Codes, provide basic norms, regulations and conducts linked to the fundamental beliefs or values of the profession, which are undertaken through the professional socialization that one student experiences when taking part in an environment of practice [44,45]. Thus, the evaluation of skills and competences, both in the academic and clinical environments, should emphasize the estimated value of these behaviors [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the importance to students of gaining clinical competency during internship has already been pointed out in various studies 9 , 10 , 11 ) . In addition to this competency, professionalism 12 , 13 , 14 ) as a physical therapist, including the motive for becoming one, should be carefully considered for effective internship.…”
Section: Discussionmentioning
confidence: 99%